Analisis Sistem Informasi Akuntansi Pengelolaan Zakat pada BAZNAS Kota Binjai - Cindy Purnama Asry Nasution; Hendra Hermain; Wahyu Syarvina (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This study aims to analyze how the Accounting Information System is applied to BAZNAS Binjai City. This type of research is qualitative descriptive by using interview, observation, and documentation techniques as data collection techniques. The results of this study show the realization of the Accounting Information System at BAZNAS Binjai City with the standard that has been written in PSAK 109 and has been well computerized so that it can produce information about the utilization of zakat in BAZNAS Binjai City for the community. This study also shows how the form of zakat fund management in BAZNAS Binjai City with recognition, measurement, presentation and disclosure in accordance with PSAK 109 as the main basis for zakat fund management regulations that have been stipulated by Law No. 23 of 2011. While the knowledge of the people of Binjai City about zakat management institutions such as BAZNAS Binjai City can affect the trust of muzzaki candidates in BAZNAS Binjai City to entrust their zakat to BAZNAS Binjai City.